Investigating Effects of Small-Group Student Talk on the Quality of Argument in Chinese Tertiary English as a Foreign Language Learners’ Argumentative Writing - Li, Hui Helen; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
Previous studies have offered a rationale for engaging students in small-group student talk for the planning of L2 individual writing. To further investigate whether such talk effectively promotes the quality of argument in the context of Chinese tertiary EFL learners’ argumentative writing and whether such effects could be retained, the current study adopted a quasi-experimental design with a pretest, a posttest, and a delayed posttest in two intact EFL classes. The performance of the intervention group and the comparison group were scrutinized to examine the effects of the intervention. The analytic scores on six components of the writing task (claim, data, counterargument claim, counterargument data, rebuttal claim, rebuttal data) and the holistic writing scores cumulated of all these components were measured to see the immediate and sustained effects. Significant changes of the holistic scores in both the immediate posttest and the delayed posttest indicated that such small-group student talk enabled students in the treatment class to achieve better performance in the overall quality of argumentation compared with those in the comparison class. Statistical analyses revealed immediate and sustained effects of small-group student talk on the quality of counterargument claim, counterargument data, and rebuttal claim. Counterargument claim was the only element in which students in both classes made significant improvement, but the treatment class demonstrated a larger effect size. No discernible differences were found either between or within the treatment class and the comparison class with respect to the quality of claim, data, and rebuttal data across tests. Possible explanations concerning the findings and limitations of the study were discussed.